Language Attitudes: Convergence and Divergence in the Political Speeches of Imran Khan - Saeed, Nimra; Nayab, Durr e (Pakistan Languages and Humanities Review, 2025)
The current study analyzes the convergence and divergence techniques employed in political speeches by Imran Khan and investigate a wide range of Khan’s comments from his various election rallies, sessions conducted during his government and foreign conferences from the year 2018 to 2022 using Communication Accommodation Theory (CAT). Drawing on qualitative content analysis, the study examines a purposive sample of political speeches delivered both domestically and internationally. Language used by Khan is very purposeful and clearly indicates language attitudes; convergence and divergence. Convergence is employed to show a sense of solidarity and unity whereas divergence is used for the sake of distancing oneself. Khan through his patriotic metaphors and Urdu language represents him as the leader of the common people while he employs divergence to distance himself from the foreign powers. This shows clearly how these language attitudes create versatile yet contextual ideologies in the politics of South Asia